Two new species of Plistobunus from China (Opiliones: Laniatores: Epedanidae) - Gong, Xuyun; Kury, Adriano B.; Zhang, Chao (Zootaxa, 2021)
The present paper describes two new species of Plistobunus Pocock, 1903, from China: Plistobunus gracilipenis sp. nov. from Yunnan Province, and P. weiguang sp. nov. from Guangxi Province. Their discovery greatly expands the distribution of this genus to the northwest and further inland in China.